Eksplorasi Dampak Kecanduan Media Sosial terhadap Religiusitas Mahasiswa dan Strategi Mitigasinya di Era Digital - Hidayah, Susilo; Syafiq, Salsabila Nafis Raihanah; Fahreza, Muhammad; MZ, Riza Arif (Moderasi : Journal of Islamic Studies, 2025)
The purpose of this study was to analyze how social media addiction affects the level of religiosity of students at SMKN 5 Malang. The development of technology is very rapid and strategic in the era of the current generation is increasingly advanced so that it cannot be denied with the support of the internet for social media so that people now cannot be separated from social media, especially in adolescence, which has an impact on disrupting learning activities in schools. Therefore, the need for a balance between imtek and imtaq education in the hope of being able to help the current generation to optimize and use social media wisely, especially in increasing religiosity among students. This research uses a qualitative approach with the type of field research. The negative effects of social media addiction on student religiosity include the negative influence of content, imbalance in time management and focus, and lack of social interaction. And the positive effects of social media on student religiosity are being able to access and disseminate positive information, being able to access religious content, and getting motivation and inspiration. The strategies carried out by teachers and students in overcoming social media addiction to student religiosity at SMKN 5 Malang are limiting the time of use in social media, always spreading or accessing positive content, holding socialization activities, keeping themselves busy with other activities, and mingling with people around both family, friends, or society.